2015
DOI: 10.1007/s11356-015-4923-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atrazine on photosynthesis and defense response and the underlying mechanisms in Phaeodactylum tricornutum

Abstract: Atrazine (ATZ) is a commonly used herbicide that has recently come under scrutiny due to potential environmental toxicity and contamination. In this study, we found that the administration of ATZ indeed leads to reduction of photosynthesis and oxidative stress in Phaeodactylum tricornutum at the treated doses higher than 100 μg L(-1) after 48 h. We further explored the effect of ATZ on photosystem II (PSII) and gene expression of electron transport chain. Collectively, our results may suggest that ATZ entered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Bai, X. et al . suggested that atrazine entered the chloroplasts depending on its liposolubility and directly attacked on the electron transport chain, especially PSII, contributing to reactive oxygen species (ROS) burst 27 . Then expression of ROS-related genes and activities of ROS-scavenging enzymes gave an integrative view of physiological state and detoxifying potential under conditions of sensitivity or tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bai, X. et al . suggested that atrazine entered the chloroplasts depending on its liposolubility and directly attacked on the electron transport chain, especially PSII, contributing to reactive oxygen species (ROS) burst 27 . Then expression of ROS-related genes and activities of ROS-scavenging enzymes gave an integrative view of physiological state and detoxifying potential under conditions of sensitivity or tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10.4 Gb was used for de novo transcriptome assembly, resulting in a comprehensive data set for the identification of genes corresponding to atrazine stress in the AM association. The objective of this work was to prove AMF has important ecological significance on atrazine degradation 9 10 11 , and provide evidence for the molecular mechanisms of atrazine degradation by AMF 27 28 .…”
mentioning
confidence: 99%
“…Few studies in mammals have however investigated the effect of atrazine on metabolism and liver function (26,(30)(31)(32)(33), especially with respect to the effects of chronic prolonged exposure (longer than 3 months) (28), and no studies have examined effects of exposure prior to birth on offspring metabolism. This is surprising, given the main use of atrazine as a herbicide in agriculture is to disrupt the photosynthetic metabolism of plants (34). Interestingly, in the USA there is a considerable amount of overlap in areas of high atrazine use and obesity prevalence in humans (28,35).…”
Section: Introductionmentioning
confidence: 99%
“…The role of the SDHA protein is as an electron transporter associated with Complex II of the mitochondrial electron transport chain, part of the tricarboxylic acid (TCA) cycle, which releases ATP through the oxidation of fats (Kay and Weitzman 1987). Because the action of ATZ is to disrupt analogous complexes in the electron transport chain of plants, specifically Photosystem II (Bai et al 2015), it is not surprising that ATZ can affects Sdha expression in mammals. Equally, Nrf1 functions as a transcription factor that activates the expression of metabolic genes and those critical in mitochondrial DNA replication and function (Scarpulla et al 2012).…”
Section: Discussionmentioning
confidence: 99%